Consciência religiosa e secularismo a partir de John Finnis - Bertoncello, Leandro da Silva (Universidade do Vale do Rio dos Sinos, 2019)
This dissertation aims to investigate the theory of natural law elaborated by John Finnis to demonstrate how religion constitutes a basic good for human flourishing, deserving expression and acceptance in the public sphere of a secularist society. It is a matter of recognizing the public status of religiously based arguments that make them capable of being accepted as rational and not just religious faith positions, being defended in terms compatible with the current secularist milieu, where the existence of God is characteristically denied or regarded as irrelevant to the practical affairs of the social sphere. Bibliographic review is used as a method, by means of collecting the material written by Finnis, as well as other works related to the theme here, with the analytical approach and interpretation of the ideas obtained in these diverse sources. Finnis's theory on natural law is studied, with emphasis on the new interpretation of the first principle of practical reasonableness made by Germain Grisez and the ensuing discussions. We investigate the conformation of secularism as a prevailing mentality that denies or neglects causes and transcendent ends for human pretensions. Finnis's reflections on religion as a rational harmony between faith and the actions of the religious individual are analyzed. It is concluded, with the results obtained, that there is no basis in claiming to exclude from the public sphere the claims based on the religious conscience, even in the case of a secularist environment, since they are claims elaborated according to criteria of practical reasonableness and that they concern the authenticity of human beings, and it is not yet justified to claim that religious persons restrict to their intimacy the fundamental human good of religion and yield to secularist positions contrary to their conscience.
Keywords: John Finnis; Lei natural; Secularismo; Consciência religiosa; John Finnis; Natural law; Secularism; Religious conscience; ACCNPQ::Ciências Humanas::Filosofia